Beyond Representation in Contemporary Caribbean Art : Space, Politics, and the Public Sphere - Garrido Castellano, Carlos (Book collections on Project MUSE., 2019)
The Caribbean has been traditionally associated with externally devised mappings and categories, thus appearing as a passive entity to be consumed and categorized. Challenging these forces and representations, Carlos Garrido Castellano argues that something more must be added to the discussion in order to address contemporary Caribbean visual creativity. Beyond Representation in Contemporary Caribbean Art arises from several years of field research and curatorial activity in museums, universities, and cultural institutions of Jamaica, Trinidad, Martinique, Guadeloupe, Cuba, Dominican Republic, Puerto Rico, and the United States. This book explores the ways in which Caribbean individuals and communities have recurred to art and visual creativity to create and sustain public spaces of discussion and social interaction. The book analyzes contemporary Caribbean art in relation to broader discussions of citizenship, cultural agency, critical geography, migration, and social justice. Covering a broad range of artistic projects, including curatorial practice, socially engaged art, institutional politics, public art, and performance, this book is about the imaginative ways in which Caribbean subjects and communities rearrange the sociocultural framework(s) they inhabit and share.